Interleukin-13 maintains the stemness of conjunctival epithelial cell cultures prepared from human limbal explants. - Andrea Stadnikova; Peter Trosan; Pavlina Skalicka; Tor Paaske Utheim; Katerina Jirsova (PLoS ONE, 2019)
To use human limbal explants as an alternative source for generating conjunctival epithelium and to determine the effect of interleukin-13 (IL-13) on goblet cell number, mucin expression, and stemness. Human limbal explants prepared from 17 corneoscleral rims were cultured with or without IL-13 (IL-13+ and IL-13-, respectively) and followed up to passage 2 (primary culture [P0]-P2). Cells were characterized by alcian blue/periodic acid-Schiff (AB/PAS) staining (goblet cells); immunofluorescent staining for p63α (progenitor cells), Ki-67 (proliferation), MUC5AC (mucin, goblet cells), and keratin 7 (K7, conjunctival epithelial and goblet cells); and by quantitative real-time polymerase chain reaction for expression of the p63α (TP63), MUC5AC, MUC4 (conjunctival mucins), K3, K12 (corneal epithelial cells), and K7 genes. Clonogenic ability was determined by colony-forming efficiency (CFE) assay. Using limbal explants, we generated epithelium with conjunctival phenotype and high viability in P0, P1, and P2 cultures under IL-13+ and IL-13- conditions, i.e., epithelium with strong K7 positivity, high K7 and MUC4 expression and the presence of goblet cells (AB/PAS and MUC5AC positivity; MUC5AC expression). p63α positivity was similar in IL-13+ and IL-13- cultures and was decreased in P2 cultures; however, there was increased TP63 expression in the presence of IL-13 (especially in the P1 cultures). Similarly, IL-13 increased proliferative activity in P1 cultures and significantly promoted P0 and P1 culture CFE. IL-13 did not increase goblet cell number in the P0-P2 cultures, nor did it influence MUC5AC and MUC4 expression. By harvesting unattached cells on day 1 of P1 we obtained goblet cell rich subpopulation showing AB/PAS, MUC5AC, and K7 positivity, but with no growth potential. In conclusion, limbal explants were successfully used to develop conjunctival epithelium with the presence of putative stem and goblet cells and with the ability to preserve the stemness of P0 and P1 cultures under IL-13 influence.